Selection of High School Majors using a Decision Support System for Students at SMPN 210 Jakarta Using the Profile Matching Method - Julisawati, Elly Agustina; Hurnaningsih; Mardiyati, Sri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The selection of a high school major is a pivotal decision that profoundly impacts a student's prospects. This research endeavors to enhance this decision-making process by introducing a Decision Support System (DSS) employing the Profile Matching Method at SMPN 210 Jakarta. The Profile Matching Method is meticulously crafted to offer personalized major recommendations based on students' interests, skills, and aspirations. Employing a quantitative approach, the study scrutinizes student data alongside major prerequisites to formulate a streamlined DSS. The research findings underscore that the application of the Profile Matching Method within a DSS empowers students to make well-informed decisions, streamlines the major selection process, and optimizes the utilization of educational resources within SMPN 210 Jakarta. This implementation holds the potential to foster positive transformations in high school major selections and fortify educational advancements at SMPN 210 Jakarta.